The Annual of The NORTH DAKOTA Agricultural College 1914 - Football (4) - North Dakota Agricultural College (Fargo, N.D.); Fargo (N.D.); (North Dakota State University Library, University Archives;, 1914)
THE 1914 AGASSIZ 204 "kid" his opponents generally furnishing them with excellent entertainment, besides considerable worry through his tact in breaking through the line. His smiles and inspiring countenance will be missed on the team. GROVER C. EDWARDS, captain of the 1913 squad, and one of the old stars had the misfortune of spraining his ankle during practice in the early part of the season and therefore was unable to get into the game, much to his own regret. However, he watched the games with a mingled sense of "love and hatred." He is a junior in the course of Agriculture and the strongest defensive player on the team. LLOYD KELLY is a sophomore in the Engineering course and has been with the team two years. Kelly is a reliable linesman and can hold his own against anyone. His weight of body and cool head enable him to play a cool, heady, and consistent game. He hails from the Hawkeye state, where he received his early training. During the season of 1911 he was out of the game because of injuries, only to come back this year stronger than ever. He is a very creditable player and a valuable cog in the football wheel. "DICK" BJORNSON just finished his first year on the team. He played guard, and developed considerably during the latter part of the season. "Dick" originally came from Iceland but has become sufficiently Americanized to attend the A. C. He graduates from the A. & M. T. High School this year and we expect to see him a strong factor on the A. C. football team for years to come. FRED HACKETT, a senior in the course of Chemistry, has been with us two seasons and has added strength and ability to the team. He and Gulbrandson alternate at center. Fred has a peculiar method of stopping the ball before it leaves the quarterback, much to the chagrin of the opposing center. He is a powerful defensive player and a sure tackler anywhere. Fred received his football tactics at the Wahpeton Science School and made the all-State team in 1910. MELVIN OSTBY, junior in the Agricultural Course is always ready when called upon to go into the game with all the vim and vigor he can muster. He is a very reliable end man, strong on defensive, but does not make any grand stand plays; is one of the most conscientious players on the squad. He was the only junior on the team in 1912. Viewbooks; 27 x 20 cm. Title taken from cover of book